A critical investigation of a planned organisation change initiative within an educational institution in the Eastern Cape Province - Irvine, Margaret Hillian (Rhodes University, Faculty of Education, Department of Education, 2000)
South Africa is living is turbulent times at present. Non-government educational organisations are challenged by changes in education policy and by scarcity of donor funding for their work. This study focuses on the management of organisation change in a non-government organisation (NGO) working in rural areas of the Eastern Cape Province. I undertook the research to gain a clearer understanding of the management of organisational change. I used a third-wave change management approach, the future search conference, to conduct the process of change with the NGO. It focuses on the positive aspects of the organisation, its potential and its desired future. I conducted both the study and the future search conference as participatory action research, which involved the participants in the cycles of planning, action, observation and reflection and thus built ownership of the solutions they generated. I used the accounts of the activities arising from the future search conference, minutes of meetings, semistructured interviews and observation of behaviour to gather data. I analysed the data using triangulation, and in particular, space triangulation, to minimise the impact of the differences in culture and language use in the facilitator and participants. Analysis of the data collected revealed in the NGO that change and transformation are slow processes requiring ongoing support from the OD consultant. The staff defined organisational effectiveness, the goal of organisational change initiatives, in terms of fundraising ability. This ability embraces many of the qualities of a learning organisation and open systems thinking, two requirements for successful organisational change. In the NGO both organisation development and transformation were processes as well as products, and changes could not easily be measured until after the processes were completed. Organisational culture, and in particular the juxtaposition of the values of the organisation and staff and those of its partners and clients, played an important role in transformation. The differences lay in a 'being' and a 'task' orientation and the staff's responsibility lay in building connections between the two. The staff received the approach of the future search conference well and there was an equally good fit between the future search conference and participatory action research. This needs to be investigated further with regard to change management in South African organisations.
Keywords: School management and organization -- South Africa -- Evaluation; Education and state Educational change -- South Africa -- Eastern Cape; Education -- Economic aspects; Organizational change -- South Africa -- Management; Non-governmental organizations -- South Africa -- Eastern Cape; School management and organization -- South Africa -- Eastern Cape